TERT promoter mutations in melanoma survival. Issue 1 (2nd March 2016) - Nagore, Eduardo; Heidenreich, Barbara; Rachakonda, Sívaramakrishna; Garcia‐Casado, Zaida; Requena, Celia; Soriano, Virtudes; Frank, Christoph; Traves, Victor; Quecedo, Esther; Sanjuan‐Gimenez, Josefa; Hemminki, Kari; Landi, Maria Teresa; et al.
Abstract : Despite advances in targeted therapies, the treatment of advanced melanoma remains an exercise in disease management, hence a need for biomarkers for identification of at‐risk primary melanoma patients. In this study, we aimed to assess the prognostic value of TERT promoter mutations in primary melanomas. Tumors from 300 patients with stage I/II melanoma were sequenced for TERT promoter and BRAF/NRAS mutations. Cumulative curves were drawn for patients with and without mutations with progression‐free and melanoma‐specific survival as outcomes. Cox proportional hazard regression models were used to determine the effect of the mutations on survivals. Individually, presence of TERT promoter and BRAF/NRAS mutations associated with poor disease‐free and melanoma‐specific survival with modification of the effect by the rs2853669 polymorphism within the TERT promoter. Hazard ratio (HR) for simultaneous occurrence of TERT promoter and BRAF/NRAS mutations for disease‐free survival was 2.3 (95% CI 1.2–4.4) and for melanoma‐specific survival 5.8 (95% CI 1.9–18.3). The effect of the mutations on melanoma‐specific survival in noncarriers of variant allele of the polymorphism was significant (HR 4.5, 95% CI 1.4–15.2) but could not be calculated for the carriers due to low number of events. The variant allele per se showed association with increased survival (HR 0.3, 95% CI 0.1–0.9). The data in this study provide preliminary evidence that TERT promoter mutations in combination with BRAF / NRAS mutations can be used to identify patients at risk of aggressive disease and the possibility of refinement of the classification with inclusion of the rs2853669 polymorphism within TERT promoter. Abstract : What's new? Mutations in the promoter of the TERT gene lead to increases in telomerase activity, prolonged telomere maintenance, and cell immortality. Such mutations are associated with parameters of adverse outcome in different cancer types, including melanoma. Data from this study shows that in primary melanoma, mutations in the TERT promoter together with mutations in BRAF/NRAS are associated with very poor survival and can be used to identify patients at risk of disease relapse and death. The prognostic value of the mutations is potentially improved through inclusion of a common polymorphism harbored within the TERT promoter.